ANALISIS PENGARUH GAYA HIDUP DIGITAL TERHADAP MANAJEMEN KEUANGAN PRIBADI MAHASISWA/MAHASISWI AKUNTANSI FEB UDAYANA AKT. 2024-2025 - Gendhis Cloaudia; Yohana Fransiska; Primesty Ardhia; Indika Sulistiana; I Ketut Wahyu; Maxi Millian; Darryl Denver; Roby Zanamba (Jurnal Riset Multidisiplin Edukasi, 2025)
This research endeavors to scrutinize the effects of a technology-driven way of life on how accounting students at Udayana University's Faculty of Economics and Business handle their finances during the academic period of 2024 to 2025. A quantitative research design is employed, utilizing survey questionnaires distributed to a sample group of 30 individuals. Simple linear regression was used to analyze the accumulated data. The outcomes demonstrate that a digital lifestyle has a noteworthy impact on how students manage their own money. A greater reliance on digital platforms like electronic wallets, online shopping sites, and social networking generally corresponds to a decline in their ability to manage personal finances effectively. It is anticipated that these observations will provide insights for learning institutions and students alike, with the goal of strengthening financial knowledge in this digital age.